2017
DOI: 10.12783/dtssehs/eemt2017/14542
|View full text |Cite
|
Sign up to set email alerts
|

Employee Engagement and Job Performance of Employees—a Study from Hospitality and Tourism in Hainan

Abstract: Abstract. The study was taken assess the effect of Vigor, Dedication and Absorption dimensions of Employee engagement on the Job performance of the employees and its implication on this industry. Data was collected from manager/senior executives and supervisors/junior executives by administering them structured questionnaire on employee engagement and job performance. Data analyses & interpretation was done by using simple percentage, Pearson Correlation and One Way ANOVA. Correlation analysis reveals that vig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 3 publications
2
5
1
Order By: Relevance
“…The results from Fauzi & Ed's research (2016) which argues that dedication has a positive and significant affect on employee performance and has a great contribution to influence was inline with the research results from Fan & Cai (2017) which shows that dedication has a positive and significant affect on task performance and contextual performance. While the research results from explained that dedication has significantly contributes to employee performance.…”
Section: Literature Review Employee Performancementioning
confidence: 53%
See 1 more Smart Citation
“…The results from Fauzi & Ed's research (2016) which argues that dedication has a positive and significant affect on employee performance and has a great contribution to influence was inline with the research results from Fan & Cai (2017) which shows that dedication has a positive and significant affect on task performance and contextual performance. While the research results from explained that dedication has significantly contributes to employee performance.…”
Section: Literature Review Employee Performancementioning
confidence: 53%
“…In addition, the company were also expected to be able to create an extra value to excel in competition, including in the field of human resources (Nawangsari & Sutawidjaya, 2019) Several previous research have shown the variations in the affect of vigor, dedication and absorption towards employee performance. The research results from Javed & Cheema (2015); Fan & Cai (2017); ; Jaya & Dawood (2020); Gil et al(2020) which stated that vigor has a significant affect on performance. The Research which conducted by Lewiuci et al (2016); Carter et al (2016); Meilia & Setyowati (2016), Meswantri & Awaludin (2018) and Bilal et al (2019) revealed that dedication has a significant affect on performance.…”
Section: Introductionmentioning
confidence: 99%
“…This logic is supported by research results which state that vigor has a significant positive effect on employee productivity [6], performance [8], contextual and task performance [11].…”
Section: B Effect Of Vigor On Employee Performancementioning
confidence: 74%
“…There are results which state that vigor on performance has a very weak significant positive effect [6], a weakly significant positive [7], [8] and a moderately significant positive [9], [10]. Dedication on performance has a weakly significant positive effect [10], a moderately significant positive [7]- [9], [11], and a significant positive [6], [12]. Meanwhile, absorption on performance has a very weak positive significant effect [6], [13], a weak positive significant [10], a moderate positive significant [7], [8], [11], and a significant positive [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation